Portraits of Women in the New Order Era - Azizah, Riva (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2025)
Women have an important role in the process of forming a new civilization, because it is from women that the new generation receives education. It is not surprising that the lack of progress of women influences whether or not a nation develops or progresses. In Indonesian history, women have had their own dynamics in their historical role; women's participation in all aspects of national and state life cannot be ignored. Even though the majority of women in Indonesia are under patriarchal domination, in line with the demands of the times and the real conditions of the surrounding environment, women are also required to play an active role in the public sector. This research uses a qualitative approach with document analysis methods as a data collection instrument.